The Perception of Investors on Socially Responsible Investment: International Evidence - Chiew, Dominic Kia Seng (2008)
It is quite impossible to deny the growing importance of socially responsible investing (SRI) since its introduction in the early 1990s (Robson and Wakefield, 2007), when little attention was paid to this subject within the business ethics community as an alternative outlet to the existing conventional investment philosophy (Sparkes, 2001). The increasing use of Socially Responsible Investment (SRI) in the financial markets has become more apparent today. Organization have included many other methods to improve earnings and improve methods business is done. The use of corporate social responsibility (CSR) and SRI have gain great amount of interest in corporate and education institutions. The inception of SRI in the 1990s has triggered numerous researches into alternative investment philosophies. SRI, which builds upon its ecological beginning and religious roots, has influenced the perceptions, preferences and choices of investors and fund management institutions. This, in turn, has altered their financial asset selection strategies to either hold SRI funds in its entirety or to include some SRI funds into their investment portfolios. The objective of this study is to identify and compare the divergent perceptions on SRI across demographic factors (such as education, income, gender and internet access) in influencing the perception of ordinary investors and socially responsible investors across demographic level and towards the corporate social responsibility (CSR) position held by the companies. Besides that, how businesses function hinges on the legal environment it operates in. As such, this study will also look at how legal traditions of countries will influence the perception of general investors and socially responsible investors towards the CSR position held by the companies. The collective data on individual SRI investors are not readily available. This study uses a questionnaire, which consist of a list of questions asking respondent, developed by GlobeScan. The reason GlobeScan Ltd is used due to its reputation and extensive source of survey information available on SRI. GlobeScan Ltd had first published this survey during the Environics Millennium Poll in 2000. In each consecutive year thereafter, the survey samples a wide coverage of around 1000 respondents in each of a wide selection of countries around the world. A survey was done from 20 countries on 2003. There are 20993 observations from 20 different countries. From the findings in this study, it is found that a company social environment performance is generally not as important as financial performance in terms of education level and income level and internet access is rejected. Gender type has rather mixed views and is significant for all investors but not for SRI investors. Similarly, the legal traditions there are mixed in views that a company’s social and environmental performance is not as important as its financial performance. On the response for socially responsible companies are more profitable than socially irresponsible companies, education level and internet access is significant while income level is mixed in responses and gender type is rather neutral in differences. Legal tradition have mixed view on the idea that socially responsible are more profitable that socially irresponsible companies. Furthermore, for the question that companies should to be more responsible to their shareholder than the broader society, education level, income level and internet access matters while gender type and legal tradition have mixed views. Finally, on the basis that to trust the accuracy of the financial statement of companies, education level, income level and gender type does not matter while internet access views in not significant for SRI but weak for all investors. Subsequently legal traditions have mixed views.